1993
DOI: 10.1073/pnas.90.3.1009
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of serine protease activity by aluminum: implications for Alzheimer disease.

Abstract: The brain of Alzheimer disease patients contains plaques that are diagnostic for the disease. The plaques also contain (-amyloid peptide, a1-antichymotrypsin, and the element aluminum. We present indirect evidence that can relate all three components of plaques to each other in such a way as to suggest their involvement in the etiology of the disease. The P-amyloid peptide is derived by proteolytic processing from 3-amyloid precursor proteins and some of these proteins contain a domain that is highly homologou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Al, a non-transition metal, is also known to enhance the processing of APP. It has been shown by Clauberg and Joshi [79] that Al accumulated in AD brain accelerates the generation of Ab due to the faulty proteolysis of normal APP [79]. It has been shown that APP has a domain homologous to bovine pancreatic trypsin inhibitor, and the activity of serine protease inhibitors is inhibited by Al.…”
Section: Al and Ab Bmentioning
confidence: 99%
“…Al, a non-transition metal, is also known to enhance the processing of APP. It has been shown by Clauberg and Joshi [79] that Al accumulated in AD brain accelerates the generation of Ab due to the faulty proteolysis of normal APP [79]. It has been shown that APP has a domain homologous to bovine pancreatic trypsin inhibitor, and the activity of serine protease inhibitors is inhibited by Al.…”
Section: Al and Ab Bmentioning
confidence: 99%
“…Most resorbed aluminum is excreted; the non-excreted part is largely deposited in bone. Some resorbed aluminium leaks slowly into the cells and may interfere with the transcription of DNA (Lukiw et al 1992), increase the production of beta-amyloid from the amyloid precursor protein (Clauberg andJoshi 1993, Zatta et al 1993). induce aggregation of the beta-amyloid (Mantyh et al 1993, Kawahara et al 1994, Exley et al 1995 and contribute to the formation of neurofibrillary tangles (Shin et al 1995, Zatta 1995.…”
mentioning
confidence: 99%
“…The obtained activation of pepsin is probably a consequence of conformational changes of enzyme molecule induced by bounded aluminium. As it were previously reported in analogy to the other aspartic proteases, bounded aluminium ions could causes significant conformational changes and induce increase in beta structure content (Flaten et al 1992, Bittar et al 1992, Clauberg et al 1993). …”
Section: Resultsmentioning
confidence: 87%